Efektifitas Metode Hypnoteaching untuk Meningkatkan Kemampuan Belajar Berhitung pada Anak Kelompok B di TK An-Nur Perumahan Griya Srimulya Palembang - Erni Muliddya; Taty Fauzi; Rahmah Novianti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to determine the effectiveness of the implementation of the Hypnoteaching in Improving the Learning Ability to count in Group B Children in An-Nur Kindergarten, Griya Srimulya Housing, Palembang. This research was conducted in An-Nur Kindergarten, Griya Mulya Housing, Palembang City. The time of the research was carried out in the academic year 2021-2022, starting from March-April-May 2022. The study took the type of cluster sampling, the research sample was divided into 2 classes, the experimental class, and the control class. the number of samples in this study was 15 students in class B2 in the experimental class and in-class B1 as many as 15 students in the control class. In this study, the t-count results were 2.898 where the t-table value was 2.131 at a significance level of 0.05 and with a one-sided test. Because the t-value obtained is greater than the t-table value of 2.898 > 2.131, the null hypothesis (Ho) is rejected and the alternative (Ha) is accepted. This means that there is effectiveness in increasing early childhood numeracy skills by using the hypnoteaching in An-Nur Kindergarten, Griya Srimulya Housing, Palembang.